Oncology Nurses’ Attitudes, Knowledge, and Practices in Providing Sexuality Care to Cancer Patients: A Scoping Review - Omar Alqaisi; Maha Subih; Kurian Joseph; Edward Yu; Patricia Tai (Current Oncology, 2025)
Sexual health in cancer care is often overlooked. This study examines oncology nurses’ knowledge and practices regarding sexuality care, identifying barriers and facilitators. A Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA)-guided search of Scopus, ScienceDirect, PubMed, and EBSCO focused on studies from 2014 to 2024. Of 1735 identified studies, only 11 met inclusion criteria. Findings revealed a lack of knowledge among nurses and dissatisfaction with sexual healthcare. Barriers include time constraints, cultural factors, and personal reservations. Routine discussions are often absent due to inadequate training. Education- and system-based strategies are needed to enhance nurses’ competence in addressing sexual concerns. Implementing training programs, structured records, evaluation tools, concept maps, and system support would improve patient care and oncology nursing practices. Addressing these gaps with practical measures can enhance communication, patient satisfaction, and quality of life. This unique analysis was conducted by two experienced advanced nurses in the Middle East, where discussions about sex are often regarded as taboo.